Faktor-Faktor Yang Mempengaruhi Penerapan Nilai-Nilai Murni di Kalangan Pelajar-Pelajar - Tan, Ai Lee (1995)
This study aims to determine the factors affecting the assimilation of noble values among students. The factors studied include the influence of parents, peer group, mass media, the influence of teacher as role model and the influence of teaching by the teacher. A questionnaire survey involving a sample of 341 Form Four students at all Government aided Secondary School in the Lower Perak District was administered. The results indicate that the influence of parents, the influence of teacher as role model and the influence of teaching by the teachers were positively and significantly associated with the assimilation of noble values among students. The findings also suggest that the influence of mass media was negatively and significantly related to the assimilation of noble values among students. It was found that there was no significant relationship between the influence of peers with assimilation of noble values among students. The findings also shows that there is a significant difference among various sexes, races and religious beliefs of the students with regards to the assimilation of noble values. However, there is no significant difference in the assimilation of noble values among students whose parents are different in terms of occupation, monthly income and level of education. The study shows that it is important to ensure that the implementation of noble values education carried across the curriculum, of a strictier school regulation system, of beneficial co-curriculum activities and the collaboration among the school, the family and the community be carried out more effectively.